Features of space solar power station control system - Yermoldina, G.T.; Suimenbayev, B.T.; Sysoev, V.K.; Suimenbayeva, Zh.B. (Acta astronautica, 2019)
The article is devoted to the creation of a control system for the orbital segment of a space solar power station and the main principles of its creation. The simulation of the functioning of a demonstrational space solar power station operating in an elliptical orbit with the energy transfer in low orbit sections has been conducted and a high-precision control of the spacecraft at low altitudes has been considered. The result of the performed studies is the computational confirmation of the capabilities of the measuring, calculation and orientation to provide the required accuracy of the spacecraft orientation for demonstrating the energy transfer from orbit to the receiver system. The obtained results give grounds for the construction of a demonstrational space solar power station in the low orbit. •The demonstration space experiment is necessary in realizing the idea of SSPS.•The main task is to accurately guide the channel of energy transfer to the rectenna.•The experiment involves the placement of energy reception points in Kazakhstan.•The pointing accuracy of energy transfer device is no more than 1.5 angular seconds.•To improve accuracy, it is advisable to switch to more precise measuring instruments.